Deposition of silver nanoparticles on polyvinyl alcohol film using electron beam evaporation and its application as a passive saturable absorber - Lokman, Muhammad Quisar; Yusoff, Siti Fatimah Az Zahra; Ahmad, Fauzan; Zakaria, Rozalina; Yahaya, Hafizal; Shafie, Suhaidi; Rosnan, Rizuan Mohd; Harun, Sulaiman Wadi (Elsevier, 2018)
This study investigated the generation of Q-switched pulse in fibre laser operation at 1550 nm wavelength region using silver nanoparticles (Ag NPs) as passive saturable absorber (SA). The Ag NP SA was prepared through the electron beam evaporation method with a thickness of 10 nm on pure polyvinyl alcohol (PVA) film. The average size of the Ag NPs was around 50 nm and the existence of silver element had been investigated by using the energy dispersive spectroscopy (EDS) technique. The modulation depth of the developed silver-based passive SA was 19% with saturation intensity of 170.26 mW/cm 2 . The laser was operated at 1560 nm centre wavelength with 3 dB spectral bandwidth of 1.3 nm. The pulsed laser was able to generate pulse energy of 146.4 nJ with peak power of 20.5 mW at a maximum pump of 90.4 mW. A signal-to-noise ratio (SNR) value of 67.5 dB was obtained at the repetition rate of 65.4 kHz for maximum input pump power.